Market valuation and M&A profitability: Short and long-term evidence from Finnish stock market - Haiko, Aki (My University, 2018)
The purpose of this study is to examine the short- and long-term acquirer profitability of the mergers and acquisitions in Finland. The profitability of mergers and acquisitions has been widely studied. The prior literature suggests that target shareholders experience positive wealth impacts after M&As, whereas for acquirer shareholders the results are more questionable. Most of the studies concentrate on US and UK markets, and thus more research for less studied Finnish markets is needed. In addition, the purpose of this study is to examine the relation between the overall market valuation levels and the profitability of the M&As, since this relation has received less empirical attention in prior M&A literature. The data used in this study consist of mergers and acquisitions announced between April 2006 and April 2015. The methodology used for the short-term returns is the event study and the two different event windows, [-1, +1] and [-10, +10], are examined. The abnormal returns for short-term returns are estimated with the market model. The long-term returns are examined with the buy-and-hold abnormal returns with matching firms. The matching firms are controlled with two indicators; size and book-to-market ratio. Statistical significance of the results is tested with the cross-sectional t-test. The results suggest that overall mergers and acquisitions announced by Finnish companies generate positive short-term abnormal returns to the acquiring company shareholders, whereas results of long-term returns remain mixed. Furthermore, the market valuation and the indicators of it does have a significant effect on the profitability of mergers and acquisitions in Finland. M&As announced during high- and low-valuation generate positive short-term abnormal returns, whereas it is more probable to experience positive long-term abnormal returns after M&A announced during low-valuation market. Contrary to expectations the number of M&As announced in high-valuation market is not higher than in other market valuation levels but actually lower.
Keywords: mergers and acquisitions; market valuation; acquirer performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|